Exploring the Molecular Basis of Anticancer Activity in Various Mushroom Species Against Colorectal Cancer Cells - Ceylan, İpek and Özerkan, Dilşad and Emin, Nuray and Akata, Ilgaz and Altuner, Ergin Murat (Letters in Drug Design & Discovery, 2024)
BackgroundMushrooms are shown to protect against the side effects of cancer. Therefore, mushrooms with proven anticancer properties and active ingredients are fascinating in the search for new cancer drugs.ObjectiveIn this study, the effects of extracts from Hericium coralloides (M1), Lactarius deliciosus (M2), Lepista nuda (M3), Pleurotus ostreatus (M4), and Suillus collinitus (M5) together on HCT116 were investigated. Mesenchymal stem cells (MSCs) were used to study the effect on healthy cells.MethodsMTT was used to determine cell viability. Dose-response curves were generated, the IC50 values of the compounds were calculated, and the effect of the extracts was compared using it. The FTIR was used to analyze the quantitative changes of the cellular components.Results and DiscussionThe evaluation of the IC50 values of all fungal species showed that they reduced the cell viability of HCT116 cells. In contrast, no significant reduction in cell viability was observed in MSCs. Changes in the ratio of cell membrane lipids, proteins, and cell nucleic acids between control and fungal-treated HCT116 cells were detected by FTIR.ConclusionMany of the chemotherapeutic agents are of plant origin, and many resources should still be explored to inhibit the side effects of cancer therapy. The data obtained through this experiment will serve as a reference for studies to be a new source of anticancer drugs in modern pharmacology.
Keywords: FTIR spectroscopy